Respon pertumbuhan setek Bud Chip Tebu (Saccharum officinarum L.) terhadap pemberian Rootone-F dengan konsentrasi berbeda - Ridawati Marpaung; Yulistiati Nengsih; Fachrory Dinata (Universitas Batanghari, 2022)
This research is entitled: Response growth cuttings Sugarcane Chip Bud ( Saccharum officinarum L. ) against gift Rootone -F with concentration different .Experiments and organoleptic tests in this study were carried out at the Faculty of Agriculture, UNBARI Jambi in the month of March – August 2022 .The research design used in this study was a completely randomized design (CRD) with one treatment factor, namely the concentration of Rootone-F with 4 levels as follows; r0 = without using Rootone – F ; r1 = 200 ppm Rotoone-F ; r2 = 400 ppm Rotoone-F ; r3 = 600 ppm Rotoone-F. research pen this using 3 replications , so get 12 units experimen, every unit test consist from 10 cuttings so that the total is 120 cuttings . on every unit test determined by random 5 plants as sample . Observed parameters : percentage life Sugarcane chip bud cuttings (%) , shoot length of sugar cane chip bud cuttings ( cm), diameter of buds from sugar cane chip bud cuttings (mm), number root ( strand ), weight dry root cane chip bud cuttings (g) . Result data study analyzed statistics use analysis variety . When on analysis variety state influence real, then next with further test DNMRT level 5%. From result study obtained that the concentration of Rootone -F had a significant effect on the percentage of survival of sugarcane chip bud cuttings , shoot length, shoot diameter, but not significantly different on the number of roots and root dry weight. Giving Rootone-F with a concentration of 400 ppm (treatment r2 ) can give the best percentage of sugarcane chip bud cuttings survival of 83.33%